2023
DOI: 10.3389/fendo.2023.1203666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium-glucose transporter 2 inhibitors on sarcopenia in patients with type 2 diabetes mellitus: a systematic review and meta-analysis

Abstract: ObjectiveSarcopenia has been recognized as the third category of disabling complications in patients with type 2 diabetes mellitus(T2DM), in addition to micro- and macrovascular complications. Sodium-glucose co-transporter 2 (SGLT2) inhibitors are innovative glucose-lowering treatments that have been shown to reduce body weight and enhance cardiovascular and renal outcomes. However, there is vigilance that SGLT2 inhibitors should be taken cautiously because they target skeletal muscle and may raise the risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…Dapa treatment for ve weeks lead to adaptive changes in skeletal muscle substrate metabolism, favoring metabolism of fatty acids and ketone bodies [32] , and Dapa treatment for 14 days in insulin-resistant individuals improved fat oxidation in skeletal muscle and mimicked the effects of calorie restriction [33] . In accordance with previous results, we observed the metabolic bene ts of Dapa treatment, including decreases in body weight, body fat, and blood lipids, an increase in urine glucose concentration, an RQ value indicative of fat metabolism, and importantly, ketogenic effects; however, we did not observe a clear improvement in muscle mass, which has been controversial in previous research [34,35] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Dapa treatment for ve weeks lead to adaptive changes in skeletal muscle substrate metabolism, favoring metabolism of fatty acids and ketone bodies [32] , and Dapa treatment for 14 days in insulin-resistant individuals improved fat oxidation in skeletal muscle and mimicked the effects of calorie restriction [33] . In accordance with previous results, we observed the metabolic bene ts of Dapa treatment, including decreases in body weight, body fat, and blood lipids, an increase in urine glucose concentration, an RQ value indicative of fat metabolism, and importantly, ketogenic effects; however, we did not observe a clear improvement in muscle mass, which has been controversial in previous research [34,35] .…”
Section: Discussionsupporting
confidence: 90%
“…SIRT1 also can regulate mitochondrial quality control by promoting mitochondrial biogenesis and facilitating the disposal of dysfunctional organelles [38] . Recent experimental evidence suggests that SGLT2 inhibitors have activating effects on SIRT1; the mechanism may involve inhibiting endoplasmic reticulum stress and oxidative stress or maintaining mitochondrial homeostasis [30][31][32][33][34][35][36][37][38][39][40][41] . We measured the RNA and protein expression levels of SIRT1 in muscle, and the results showed that it was signi cantly inhibited under high-fat diet-induced obesity conditions, while Dapa treatment had a bene cial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Mone et al reported that the SGLT2 inhibitor empagliflozin improved cognitive and physical functions [ 58 ] and mRNAs signature of endothelial dysfunction in frail diabetic patients with HFpEF [ 59 ]. However, a recent meta-analysis revealed that the use of SGLT2 inhibitors may increase the risk of sarcopenia in patients with type-2 diabetes [ 60 ]. Therefore, patients using SGLT2 inhibitors should be carefully monitored for unwanted outcomes related with muscle health.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium-glucose cotransporter 2 inhibitors that decrease proximal tubular glucose reabsorption, not only reduce body weight and body fat, but meta-analyses have indicated that they also reduce lean body mass and skeletal muscle mass. 25,26 Sodiumglucose cotransporter 2 itself is not present in skeletal muscle, and its effects on skeletal muscle may be mediated by indirect systemic effects. Possible mechanisms include decreased uptake of glucose and amino acids and increased degradation of muscle proteins in skeletal muscle associated with decreased insulin secretion, but the detailed mechanisms remain unclear (Tables 2 and 3).…”
Section: Glucose-lowering Drugsmentioning
confidence: 99%
“…Sodium–glucose cotransporter 2 inhibitors that decrease proximal tubular glucose reabsorption, not only reduce body weight and body fat, but meta‐analyses have indicated that they also reduce lean body mass and skeletal muscle mass 25,26 . Sodium–glucose cotransporter 2 itself is not present in skeletal muscle, and its effects on skeletal muscle may be mediated by indirect systemic effects.…”
Section: Drugs That Cause a Certain Frequency Of Sarcopenia Or Myopathymentioning
confidence: 99%